OVERVIEW OF MALOCCLUSION SEVERITY AND ORTHODONTIC TREATMENT NEEDS BASED ON THE INDEX OF COMPLEXITY, OUTCOME, AND NEED (ICON) IN PATIENTS AT THE UNIVERSITAS UDAYANA DENTISTRY PROFESSION CLINIC - Hutomo, Louise Cinthia; Martha, Kadek Prama Anggara; Anggaraeni, Putu Ika; Rahaswanti, Luh Wayan Ayu (E-Jurnal Medika Udayana, 2025)
Malocclusion is an abnormal occlusion that can affect facial esthetics, oral function, risk of periodontal disease, also physical and psychosocial quality of individuals. Malocclusion complexity, treatment need, and treatment success can be analyzed using the Index of Complexity, Outcome, and Need (ICON). The Dental Profession Clinic of Universitas Udayana is an educational clinic that provides health services for teeth and mouth, including orthodontic treatment using removable appliances. Patients who come for orthodontic treatment have different levels and needs of orthodontic treatment. The objective of this study is to describe the severity of malocclusion and the need for orthodontic treatment based on ICON in patients at the Dental Profession Clinic at Universitas Udayana. This study used a cross-sectional approach involving 48 samples that had appropriate to the inclusion and exclusion criteria and were selected using the purposive sampling method. The collected data were processed using descriptive statistical tests and univariate analysis. Finally, the results were presented in terms of frequency and percentage. The severity of malocclusion was mostly in the “easy” category (64.6%) and most cases of malocclusion in this study (77.1%) did not require treatment. Based on the analysis, the highest severity of malocclusion is in the “easy” category and the lowest is in the “mild” category. The level of need for orthodontic treatment showed that most of the samples did not require orthodontic treatment. Keywords : Orthodontic, Malocclusion, Index of Complexity, Outcome and Need (ICON)